Ternary functionalised carbon nanofiber/polypyrrole/manganese oxide as high specific energy electrode for supercapacitor - Mohd Abdah, Muhammad Amirul Aizat; Abdul Rahman, Norizah; Sulaiman, Yusran (Elsevier, 2019)
A successful fabrication of ternary functionalised carbon nanofibers/polypyrrole/manganese oxide (f-CNFs/PPy/MnO₂) composite was reported. The field emission scanning electron microscopy (FESEM) image had revealed a random distribution of granular PPy and spherical nanoparticles of MnO2 on the surface of f-CNFs. The measured contact angle of f-CNFs indicated superhydrophilic nature which can enhance the surface wettability and ionic diffusion. The ternary f-CNFs/PPy/MnO₂ composite displayed a remarkable specific capacitance of 409.88 F/g compared with f-CNFs/MnO₂ (322.96 F/g) and f-CNFs/PPy (290.83 F/g). The electrochemical properties of f-CNFs/PPy/MnO₂ had contributed to the appreciable specific energy of 42.53 Wh/kg at a specific power of 297.32 W/kg. The assembled f-CNFs/PPy/MnO₂ composite also showed low resistance of charge transfer (Rct) value (3.40 Ω) with a better cycle life (86.30% capacitance retention over 3000 cycles). Hence, ternary f-CNFs/PPy/MnO₂ can be suggested as a high-performance electrode for supercapacitor.